Analysis and dynamic behavior of portal structures due to reciprocating machine - Essen Donald; Dwi Pratama Andreas (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
reciprocating engine consists of two driving parts, piston and rotor, when the engine start these two parts move with a certain frequency, resulting in vibrations in the structure. dynamic analysis of the structure aim to find out how the structure behaves due to vibrations generated from the machine, whether the structure is safe for the machine and humans around the machine due to the amplitude of displacement, velocity, and displacement from structure. This dynamic analysis is carried out with the help of SAP 2000 v20.20 software with a dynamic load in the form of a reciprocating compressor operating with a frequency of 49.16 Hz. In this final project, the machine foundation uses a table top type with 1x1.7 m column dimensions and 1.3x1.6 m beams. From the free vibration analysis, the result is a natural frequency structure, from the first ten modes the structure is declared safe from resonance However, in this study the displacement and velocity of structures that occur in the zone B & C while the acceleration into the safe category based on applicable standards. This means that the structure is safe for humans who are around but are not safe for the product and the machine itself if it operates for a long time continuously.